2014
DOI: 10.1108/jkm-06-2014-0252
|View full text |Cite
|
Sign up to set email alerts
|

What matters for knowledge sharing in collectivistic cultures? Empirical evidence from China

Abstract: Purpose – The purpose of this study is to identify key factors that facilitate knowledge sharing in collectivistic cultures and further help better understand knowledge management in the international context. Design/methodology/approach – Using a survey method, this study collected data from over 200 managerial employees in knowledge management-based project teams from China. Regression analysis was then conducted to analyze the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 30 publications
1
98
2
Order By: Relevance
“…Prod., São Carlos, v. 25, n. 1, p. 1-15, 2018 ( Analoui et al, 2012;Politis, 2001), learning culture (Donate & Guadamillas, 2011;Ma et al, 2014), autonomy (Lee & Choi, 2003;Ho et al, 2014) and IT systems (Bansler & Havn, 2004;Xue et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prod., São Carlos, v. 25, n. 1, p. 1-15, 2018 ( Analoui et al, 2012;Politis, 2001), learning culture (Donate & Guadamillas, 2011;Ma et al, 2014), autonomy (Lee & Choi, 2003;Ho et al, 2014) and IT systems (Bansler & Havn, 2004;Xue et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative culture, in turn, proposes that the interests of the group and collective good take precedence over individual interests (Zheng et al, 2010). As a result, it is natural to assume that in environments where culture is collaborative, individuals are more willing to share their knowledge with the other team members, intensifying the flow of knowledge (Ma et al, 2014;Li, 2010). This discussion gives way to the third set of hypotheses:…”
Section: Learning Culturementioning
confidence: 99%
“…While collectivism facilitates trust and knowledge-sharing with "in group" members, there is usually skepticism towards "outsiders". Therefore, China remains a challenging setting for encouraging knowledge sharing amongst the workforce (Chen et al, 2010;Huang et al, 2008;Jolly, 2002;Ma et al, 2014;McAdam et al, 2012;Tong & Mitra, 2009). First, the strong emphasis on particularistic and intense social relationships (Weir & Hutchings, 2005) among Chinese workers may hinder the knowledge sharing processes.…”
Section: Cultural Barriers To Knowledge Sharing In China and Brazilmentioning
confidence: 99%
“…This could create a feedback loop such that knowledge sharing increases network involvement, thereby increasing further knowledge sharing. Additionally, while the present study examined the quality and quantity of knowledge sharing in general, managers may benefit from future studies that focus on explicit and tacit forms of knowledge sharing (see, e.g., Ma et al, 2014). …”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Although previous research has identified several key antecedents to knowledge sharing such as trust, management support, and organizational values (Connelly & Kelloway, 2003;Kankanhalli, Tan & Wei, 2005;Michailova & Minbaeva, 2012), much remains to be explored. Indeed, Ma, Huang, Wu, Dong, and Qi (2014) noted that knowledge sharing frameworks largely have their origins in Western cultures and that their application in different cultural contexts needs to be examined. Using a recently-formed regional network of corporate, civic, and nonprofit leaders in Central Eurasia as the basis for the research, this paper discusses a study that was designed to address an important question that has been understudied in past research.…”
Section: Introductionmentioning
confidence: 99%